MOCVD-grown Ga2O3 thin films for polarization-sensitive infrared photonics - Sina Abedini Dereshgi; Junhee Lee; Daniele Ceneda; Maria Cristina Larciprete; Marco Centini; Manijeh Razeghi; Koray Aydin (APL Materials, 2024)
The phonon modes of materials contain critical information on the quality of the crystals. Phonon modes also offer a wide range of polarization-dependent resonances in infrared that can be tailored to applications that require large dielectric function contrast in different crystal directions. Here, we investigate the far-field characteristics of MOCVD-grown Ga2O3 thin films. With a combination of cross-polarization FTIR and AFM characterization techniques, we propose an easy and non-invasive route to distinguish κ and β phases of Ga2O3 and study the quality of these crystals. Using numerical methods and cross-polarization spectroscopy, the depolarization characteristics of β-Ga2O3 are examined and depolarization strength values as high as 0.495 and 0.76 are measured, respectively, for 400 and 800 nm-thick β-Ga2O3. The strong birefringence near optical phonon modes of an 800 nm β-Ga2O3 on a sapphire substrate is used to obtain several polarization states for the reflected light in the second atmospheric window 8–14 µm. We anticipate that our findings open a new path for material characterization and wave plate design for the mid-IR range and offer novel possibilities for the future of IR on-chip photonics, thanks to the compatibility of β-Ga2O3 with standard nanofabrication technology.